THE POPULAR FRONT IN SPAIN: FROM AN INTERCLASS STRATEGY TO “TAKE THE SKY BY ASSAULT”. ANALYSIS OF CASE IN MURCIA ’S REAR. - González Martínez, Carmen (Revista de Historia Social y de las Mentalidades, 2024)
This article is focused on the history of the  Spanish Popular Front from its electoral  triumph in February 1936, until its final  defeat through two perspectives of analysis:  the first one is devoted to the attitude of  the Chilean and French Popular Fronts  toward the Second Spanish Republic during  the Spanish Civil War. In particular, this  study shows the effects of the defeat of the  Second Republic and the arrival of exiles  on French society. The second refers to the  overcoming of the Spanish Popular Front  as a political strategy between classes  because of their failure, the main parties  of the Popular Front, the PSOE and PCE,  tried to create an unifed party through the  liaison committees. This second perspective  is based on historical experience analyzed  in a republican rear area, the region of  Murcia. This research uses the funds of  Spanish national archives and specialized  historiography in order to illustrate and  clarify this complex period.
Keywords: Popular Fronts; Liason Committees; Murcia; Rear; Historiography; Sources